Communication between the left ventricle and right atrium. Issue 5 (September 1967) - Barclay, R. S.; Reid, J. M.; Coleman, E. N.; Stevenson, J. G.; Welsh, T. M.; McSwan, N.
Abstract : A further 15 patients with left ventricular/right atrial communication are reported, 14 of whom were treated surgically. The clinical triad of a ventricular septal defect murmur, cardiac enlargement, and an arteriovenous shunt at atrial level is characteristic of the malformation. Of the 14 patients accorded surgical treatment, one died soon after operation. The remainder are well, with both the electrocardiographic signs of left ventricular hypertrophy and the radiographic evidence of cardiomegaly having undergone regression.